Impact of Reversed Austenite on the Pitting Corrosion Behavior of Super 13Cr Martensitic Stainless Steel. (10th February 2016) - Lei, Xiaowei; Feng, Yaorong; Zhang, Jianxun; Fu, Anqing; Yin, Chengxian; Macdonald, Digby D.
Highlights: Super 13Cr with and without the reversed austenite phase was obtained. The reversed austenite distributes along the martensite lath boundaries, formed in the 620 °C-tempered specimen. The presence of reversed austenite enhances the pitting resistance of tempered Super 13Cr. TEM-EDS analysis verifies the beneficial variation of Cr, Mo, and Ni contents at the martensite/carbide/austenite interfaces, which is the main reason of the increase of pitting resistance. Abstract: Many attempts in the past have been made to introduce the reversed austenite phase into Super 13Cr martensitic stainless steel, in order to enhance its mechanical performance, but the impact of reversed austenite on the corrosion properties has not been clearly defined. To investigate the influence of reversed austenite on the pitting behavior of Super 13Cr, specimens were tempered at different temperatures to acquire microstructures without/with the reversed austenite phase. The microstructures and morphologies were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and energy dispersive spectrometry (EDS). Potentiodynamic polarization, potentiostatic polarization, and potentiostatic pulse experiments were performed in 3.5% NaCl solution, in order to characterize and analyze the pitting performance. The experimental results show that reversed austenite is distributed along the martensite laths boundaries, as formed in the 620 °C-tempered specimen. The Ni-enriched region adjacent to the carbides enables the nucleation of reversed austenite. In the presence of reversed austenite, the 620 °C-tempered specimen exhibits a higher pitting potential, lower corrosion current density, and superior metastable pitting resistance than the does 560 °C-tempered specimen (without reversed austenite), which indicates that the presence of reversed austenite enhances the pitting resistance of Super 13Cr.